Analysis Factors Associated with Functional Ability among Stroke Patients - Yanti Cahyati; Santi Wahyuni (International Journal of Nursing and Health Services (IJNHS), 2020)
Stroke is a neurological change and the primary cause of functional disorders. This study aimed to determine the factors associated with functional ability among stroke patients. A crosssectional was applied in this study. The results showed there was a relationship between muscle strength and functional capacity among stroke patients. There were significant differences in the average value of functional skills in male and female stroke patients. There is no relationship between age and functional ability. There is no difference in the average functional ability in patients with ischemic and hemorrhagic strokes, stroke patients who have comorbidities and have no comorbidities and there is no difference in the functional skills of stroke patients who experience the first attack and repeat attacks